Co-operation in agriculture and banking in British West Africa - de Graft-Johnson, John Coleman (The University of Edinburgh, 1946)
This thesis attempts to fill in one of the numerous gaps in our knowledge of the economic development of the British Colonial Empire. During the last hundred years or more, several books have been written on the geography, political history and ethnology of the component parts of the Empire. Some of these books have paid very little attention to accuracy, but the works produced in the fields referred to are so numerous that it is possible for the unbiased student in search of the truth to find the truth.

On the subject of the economic development of the Empire, however, very few books have been produced, and even these are of very recent origin. The task of building up an economic consciousness in the British Colonial Empire was first begun by the late Professor Knowles in 1924, in his book entitled "The Economic Development of the British Overseas Empire." Since then, young scholars interested in colonial economics have focused their attention on specific regions in the Empire and have produced a limited number of very useful economic books on the colonies.

Dr. Allan McPhee, a former student of Commerce and Economics at Edinburgh University, published,in 1926, the first systematic work dealing with the economic development of British West Africa. Professor Shephard, Lord Hailey, Sir Alan Pim and a few others have since. supplemented Dr. McPhee's pioneer research by publishing very useful material on the West African Colonies.

In spite of these fairly recent works, much remains to be written about the economic development of West Africa, both from a general and from a specific standpoint. An amazing ignorance still prevails in Britain about the West African colonies. The Gold Coast is commonly supposed to be in Liberia; Naorobi is regarded as being a British possession in West Africa; and Ibadan, with a population of over 300,000, and, indeed, the largest indigenous town in the whole of Africa, has never been heard of.

The time has come for more specific economic research work on the Colonial Empire to be undertaken; and in this thesis I have sought to give a comprehensive survey of the Co- operative Movement in British West Africa in so far as the movement is related to agriculture and agricultural credit.

It must be borne in mind that the Co-operative Movement in British West Africa is comparatively young, and, in fact, dates from 1929; and, What is more, the war which has just ended arrested the normal expansion of the movement. We are therefore dealing with a very young movement, a movement With great possibilities for the future prosperity of the Whole of British West Africa.

It is essential that the movement should develop along lines Which are not alien to the African peoples; and this being the case, I make no apologies for devoting the first part of the thesis to a historical survey of British West Africa. It will be necessary to give a clear picture of the African in his natural Getting and to correct certain false ideas about West Africa Which prevail at the present time. For instance there are some who believe that the African has always existed in a primitive state and is incapable of developing for himself the social and economic fabric of his society. There is no historical justification for this belief.